2014
DOI: 10.1037/a0037668
|View full text |Cite
|
Sign up to set email alerts
|

The two recollections.

Abstract: Recollection is currently modeled as a univariate retrieval process in which memory probes provoke conscious awareness of contextual details of earlier target presentations. However, that conception cannot explain why some manipulations that increase recollection in recognition experiments suppress false memory in false memory experiments, whereas others increase false memory. Such contrasting effects can be explained if recollection is bivariate-if memory probes can provoke conscious awareness of target items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
129
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(139 citation statements)
references
References 110 publications
8
129
0
2
Order By: Relevance
“…One possibility is that priming results in test items crossing the threshold for retrieval more quickly (e.g., due to priming providing items with an elevated baseline). Currently, the precise nature of recollection itself While most models consider recollection to be a univariate retrieval process responsible for retrieval of contextual details of prior episodes, it has recently been suggested that recollection is bivariate (Brainerd, Gomes & Moran, 2014). In essence, these authors distinguish between target and context forms of recollection, providing a potential explanation for the timing changes reported here: while occurring concurrently under standard recognition testing, subcomponents of recollection could be differentially engaged following priming, resulting in the observed change in onset time across conditions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that priming results in test items crossing the threshold for retrieval more quickly (e.g., due to priming providing items with an elevated baseline). Currently, the precise nature of recollection itself While most models consider recollection to be a univariate retrieval process responsible for retrieval of contextual details of prior episodes, it has recently been suggested that recollection is bivariate (Brainerd, Gomes & Moran, 2014). In essence, these authors distinguish between target and context forms of recollection, providing a potential explanation for the timing changes reported here: while occurring concurrently under standard recognition testing, subcomponents of recollection could be differentially engaged following priming, resulting in the observed change in onset time across conditions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Equally, it remains unclear whether recollection is best fractionated in terms of distinctions between item versus context information (cf. Brainerd et al, 2014), proximal versus distal cueing (cf. Moscovitch, 2008), or quantity versus quality of retrieval (cf.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…and NS? FTT assumes that the traces that are retrieved are determined by the test cue, rather than by the probe that is administered in connection with the cue (Brainerd, Gomes, & Moran, 2014). If sofa produces verbatim retrieval, regardless of whether it also produces gist retrieval, it is unambiguously identified as being a target, yielding responses to O?…”
Section: Superposition and Additive Probabilitymentioning
confidence: 99%
“…Instead, subadditivity has predominated. Brainerd et al (2010), Brainerd, Gomes, et al (2014) found that the conjoint recognition model and a related model (dual recollection) were able to fit such data for item false memory, and Brainerd et al (2012) found that the conjoint recognition model was able to fit such data for source false memory. More recently, Kellen, Singmann, and Klauer (2014) found that the two-high-threshold source memory (2HTSM) model was also able to fit such data for source false memory.…”
Section: Models That Do Not Predict Violations Of the Additive Lawmentioning
confidence: 99%
See 1 more Smart Citation